The prevalence of injury in Kendo. Issue 1 (2nd January 2016) - Schultzel, Mark; Schultzel, Matthew; Wentz, Brock; Bernhardt, Mark
Abstract: Objective : Kendo is a Japanese martial art analogous to fencing, which is becoming increasingly popular worldwide. The large number of participants creates a need to assess injury patterns to better train them. The purpose of this study is to describe current injury rates in kendo and compare these rates to other martial arts. Methods : This retrospective study used an online questionnaire sent to 500 active members of the All United States Kendo Federation and World Kendo Federation. The questionnaire, based on the NCAA Injury Surveillance System, contains questions regarding location and type of injuries sustained during competition and practice, time lost to training, and competitor demographics. Statistical analyses between competitor demographics and injury rates are provided. Injury rates are expressed as injury rates/minute of competition or practice and by athlete exposures. 95% CIs were calculated. Results : Responses from 307 of 500 kendo players were received (response rate = 61.4%). 41 (18%) male and 13 (16%) female participants reported injury to only one body region, while 16 (7%) men and one (1%) woman reported no injuries. 166 (74%) males and 70 (83%) females reported injuries to two or more body regions. The most common sites of injury involved the foot/ankle (65.1%), wrist/hand (53.5%) and elbow/forearm (48.8%). Most injuries occurred during practice (87.9% foot/ankle, 89.9% wrist/hand, elbow/forearm 92.2%). The most common injuries were contusions, abrasions, and sprains/strains. Injury rates were 121/1000 A-E (0.025 injuries/min) in tournaments versus 20.5/1000 A-E (0.011 injuries/min) in training. 26% of injuries resulted in time off of participation, with an average recovery time of 15 days (range = 1 day–1 year). Conclusions : Although more total injuries occurred in practice than in competition, there was a lower injury rate in kendo than in taekwondo and western-style fencing. This study demonstrates that kendo is a relatively safe sport compared to other martial arts sports.